Traceable Bioinspired Nanoparticle for the Treatment of Metastatic Breast Cancer via NIR-Trigged Intracellular Delivery of Methylene Blue and Cisplatin - Zhai, Yihui (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.